Environmental pollution Ecology and human health - Basha, Riyaz; Reddy, Gottipolu (ed); Reddy, Gottipolu (ed) (New Delhi Narosa Publishing House, 2012)
Early -life events trigger latent biochemical pathways for late life disorders